EXPLORATION OF ONCOLOGY HEALTHCARE PROVIDERS' KNOWLEDGE OF LESBIAN, GAY, BISEXUAL AND TRANSGENDER HEALTHCARE. (11th November 2018) - Alexander, K; Banerjee, S; Walters, C; Staley, J; Parker, P
Abstract: Cancer is diagnosed at a higher rate (53%), accounts for a higher percentage of survivors (59%) and results in more deaths among individuals 65 years and older (68%). The population at risk is growing rapidly. By 2030, the number of people aged 65 and older is projected to increase to 72 million. There are more than 3 million people in United States aged 55 and older who identify as Lesbian, Gay, Bisexual, and Transgender (LGBT). LGBT populations are at a greater risk for certain cancers compared to the general population. Healthcare providers' (HCPs') knowledge, attitude, and behavior toward LGBT patients is integral to the delivery of medically appropriate and psychosocially sensitive care. One factor that contributes to healthcare service underutilization by LGBT populations is scarcity of HCPs competent in LGBT health. In this study, we explored the knowledge of HCPs regarding LGBT patient healthcare at a Comprehensive Cancer Center, and the differences based on HCPs' demographic characteristics. An anonymous survey link was emailed to 3, 627 HCPs (physicians, Advanced practice providers and registered nurses). 1, 253 (35%) completed it. LGBT healthcare knowledge was measured by 7 items. Only 50 participants (5%) correctly answered all 7 items; and 535 respondents (50%) answered up to 3 items correctly. Demographic differences in HCP respondents - self-identification as LGBT and having LGBT friends/family – were associated with higher knowledge scores. Our findings indicate that emphasis on LGBT health care knowledge in HCP education and training, is important to increase awareness and sensitivity towards LGBT oncology patients.